ZEPHYR: failure of a “spring wind” in lung cancer - Morabito, Alessandro (Translational Lung Cancer Research, 2012)
Vandetanib is an oral inhibitor of vascular endothelial growth factor receptor-2 (VEGFR-2), epidermal growth factor receptor (EGFR) and REarranged during Transfection (RET) tyrosine kinases that are involved in tumour growth, progression and angiogenesis (1). Therefore, this drug has the advantage to contemporary block different intracellular signalling pathways, potentially providing greater benefit than blocking each pathway individually and overcoming resistance to anti EGFR therapy due to increased expression of VEGF (2,3). Four randomized phase 2 studies in patients with non-small cell lung cancer (NSCLC) showed that vandetanib prolonged progression-free survival (PFS) as single agent or when added to chemotherapy, supporting the development of the drug in phase 3 trials (4). In the article of Lee et al., the results of the ZEPHYR trial that compared vandetanib with placebo in patients with advanced NSCLC after prior therapy with one or two chemotherapy regimens and with an epidermal growth factor receptor tyrosine kinase inhibitor are presented (5). Currently, there is no approved treatment option for this widely pretreated population of NSCLC patients and effective treatments are urgently needed.